Enola Holmes Case: An Invasive Pastiche for Embodying a Holmes Sister as the Feministic Detective - Azani Fitri Gooniyah; Adeltirha Yasnu Army; Thafhan Muwaffaq (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2022)
This paper discusses about how ‘Enola Holmes’ film is a diegetic extension that represents feministic ideas. Intend to explain the relation between the feministic ideas and the concept of postmodernism. It is argued that the narrative of Enola Holmes reuses and recycles narrative of Sherlock Holmes in form of pastiche so to extend the pre-existing grand narrative of Sherlock Holmes. The extension makes it possible to render a portrayal of independent and self-determined female detective.